Determinants of Electronic Nursing Medical Record Implementation Success, Infrastructure Readiness, Digital Liteacy, and Perceived Usefulness - Farida Farida; Munawar Munawar; Kemala Rita Wahidi (International Journal of Economics and Management Sciences, 2026)
The implementation of Electronic Medical Records (EMR) is a key component of healthcare digital transformation, as mandated by the Minister of Health Regulation Number 24 of 2022. EMR is expected to enhance efficiency, accuracy, and the quality of nursing services. However, its implementation at M Hospital continues to face challenges, particularly in terms of infrastructure readiness and the digital literacy of nursing staff. This study aims to analyze the effects of infrastructure readiness and digital literacy on the implementation of nursing EMR, with perceived usefulness as an intervening variable. A quantitative cross-sectional design was employed, involving all nurses at M Hospital, with a total sample of 100 respondents using total sampling. Data were collected through structured questionnaires and analyzed using SEM-PLS. The results indicate that infrastructure readiness and digital literacy have both direct and indirect effects on EMR implementation through perceived usefulness (p < 0.05). Among the independent variables, infrastructure readiness demonstrates the strongest influence. These findings support existing theories and prior research. From a managerial perspective, the results highlight the importance of improving infrastructure to optimize EMR implementation. In conclusion, infrastructure readiness and digital literacy significantly influence the successful implementation of nursing EMR, with perceived usefulness acting as a key mediating factor.